2020
DOI: 10.3390/nu12103068
|View full text |Cite
|
Sign up to set email alerts
|

Oligo-Fucoidan Improves Diabetes-Induced Renal Fibrosis via Activation of Sirt-1, GLP-1R, and Nrf2/HO-1: An In Vitro and In Vivo Study

Abstract: Fucoidan extracted from brown algae has multiple beneficial functions. In this study, we investigated the effects of low-molecular-weight fucoidan (oligo-FO) on renal fibrosis under in vitro and in vivo diabetic conditions, and its molecular mechanisms. Advanced glycation product (AGE)-stimulated rat renal proximal tubular epithelial cells (NRK-52E) and diabetic mice induced by high-fat diet and intraperitoneal injection of streptozotocin and nicotinamide were used. Oligo-FO treatment significantly inhibited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Dietary flavone quercetin and genistein also show a benefit on endometriosis, by inhibiting the proliferation of endometriosis with the cell cycle arrest [ 32 ], and they can decrease ER-α expression and the antiangiogenics effect [ 41 ]. Fucoidan shows an anti-inflammatory effect in diabetes-induced renal fibrosis and hyperuricemia related renal damage [ 42 , 43 ] and has an anti-proliferation effect in gynecological cancer [ 29 ]. This indicates the potential effect of fucoidan on endometriosis progression.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary flavone quercetin and genistein also show a benefit on endometriosis, by inhibiting the proliferation of endometriosis with the cell cycle arrest [ 32 ], and they can decrease ER-α expression and the antiangiogenics effect [ 41 ]. Fucoidan shows an anti-inflammatory effect in diabetes-induced renal fibrosis and hyperuricemia related renal damage [ 42 , 43 ] and has an anti-proliferation effect in gynecological cancer [ 29 ]. This indicates the potential effect of fucoidan on endometriosis progression.…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1R (Glucagon-like peptide-1 receptor), which is present in various organs, such as the liver, brain and kidney, is an important pharmacological target for T2DM ( Aroda, 2018 ). A recent study showed that GLP-1R plays an important role in regulating non-diabetic and diabetic renal fibrosis Li et al (2018) , Yu et al (2020) , and Glp1r mRNA levels positively correlate with serum testosterone concentrations in normal male mice and in diabetic models ( Zhu et al, 2019 ). Research has demonstrated that miR-192 induces fibrosis in human renal tubular epithelial cells by targeting GLP-1R ( Jia et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the oligofucoidan on Nrf2 activation were inhibited, using a SIRT1 inhibitor, demonstrating that there is a crosstalk between the SIRT1 and Nrf2 cascade (Yu et al 2020). Shah et al (2017) corroborated this notion, since melatonin exerted antioxidant and anti-in ammatory activities through the Nrf2 activation, dependent on SIRT1, in the brain of immature rats and in BV2 cells.…”
Section: Discussionmentioning
confidence: 99%